PENGARUH PROGRAM PERMAINAN KOOPERATIF DALAM MENGATASI PERILAKU AGRESIF PADA ANAK DI TAMAN KANAK-KANAK ANGKASA PADANG - Putri Azura, Nabilla; Nurhafizah; Yaswinda; Yeni, Indra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Aggressive behavior in early childhood is a common social-emotional problem found in kindergartens. This behavior can include hitting, pushing, grabbing toys, screaming, and difficulty controlling emotions. This study aims to determine the effect of a cooperative play program on addressing aggressive behavior in children at Angkasa Padang Kindergarten. The study used a quantitative approach with a Nonequivalent Control Group Design. The sample consisted of 30 children divided into an experimental class and a control class, each with 15 children. Data were collected through observations of the children's aggressive behavior. The results showed that the average pre-test score in the experimental class was 16.33, increasing to 20.87 in the post-test after being treated with the cooperative play program. The independent sample t-test showed a significance value of 0.023 (<0.05), indicating a significant effect of the cooperative play program on reducing children's aggressive behavior. Therefore, cooperative play can be used as an alternative learning strategy to develop social-emotional skills and reduce aggressive behavior in early childhood.